REINTERPRETASI MAá¹¢LAá¸¤AH SEBAGAI METODE ISTINBÄ€á¹¬ HUKUM ISLAM: Studi Pemikiran Hukum Islam AbÅ« Isá¸¥Äq IbrÄhÄ«m al-ShÄá¹ibÄ« - Farih, Amin (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2015)
This article aims to analyze al-ShÄá¹ibÄ«â€™s thought about maá¹£laá¸¥ah and its contribution to the renewal of Islamic law. Maá¹£laá¸¥ah is a method of istinbÄá¹ which aims to deprive human difficulties in carrying out their obligations, especially in the field of muamalah. General principles of maá¹£laá¸¥ah that was conceived in al-Qur'an and hadis rise in the doctrine of maqÄá¹£id al-sharÄ«â€™ah. The main purpose is to enforce maá¹£laá¸¥ah as an essential element for the all purposes of Islamic law. The doctrine of maqÄá¹£id al-sharÄ«â€™ah asserted that the purpose of the law is one, namely maá¹£laá¸¥ah or goodness and prosperity of mankind. According to al-ShÄá¹ibÄ«, maá¹£laá¸¥ah which formulated the law of Islam must consider the aspects of á¸arÅ«riyyah, á¸¥Äjiyyah and taá¸¥sÄ«niyyah as a structure consisting of three tiers one of another mutually related. The significance of al-ShÄá¹ibÄ«â€™s thinking about maá¹£laá¸¥ah mursalah is that this method is a kind of unification and as an alternative over differences of opinion among the scholars on the validity of maá¹£laá¸¥ah mursalah as a method of Islamic law.